A perspective on university academic workload measurement - Cawood, Fred; Yilmaz, Halil; Musingwini, Cuthbert; Razinchenko, Galina (University of the Free State, 2008)
Internationally, universities are increasingly seen as being part of the wider community, which has an impact on academic workload. This paper explains the importance of a model for investigating such academic workloads. Quantifying and reporting workloads are complex tasks. Despite this complexity, the model developed at the University of the Witwatersrand’s School of Mining Engineering gives some insight into the three main components of academic workload, namely lecturing, research and administrative services. Today there is a better understanding of the meaning of workload, the problems to consider when quantifying workloads, the relationship between workload and performance and the issues to consider for staff development. This perspective concludes with lessons learnt over a five-year period.

Internasionaal word universiteite al hoe meer beskou as deel van die breë gemeenskap, wat ’n impak het op die werklading van akademiese personeel. Hierdie artikel sal die belangrikheid van ’n model vir die ondersoek van akademiese werklading verduidelik. Die meting en rapportering van akademiese werklading is kompleks. Ten spyte daarvan verskaf die model van die Universiteit van die Witwatersrandse Skool vir Mynbou insig in die drie hoofkomponente van akademiese werklading, naamlik dosering, navorsing en administrasie. Deesdae is daar ’n beter begrip van wat hierdie werklading behels, die moeilikhede wat oorbrug moet word by werkladingsberekening, die verband tussen werklading en prestasie, en hoe om personeelontwikkeling daarvolgens te beplan. Die perspektief sluit af met lesse geleer oor ’n vyf-jaar periode.
Keywords: Academic workload; Staff development; Workload model; Academic staff